Optimasi Parameter Produk 3D Printing Terhadap Kekuatan Bending Dengan Menggunakan Filamen Nylon - Fadhil, Irfan; Hasdiansah, Hasdiansah; Anggry, Adhe (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
3D Printing or additive manufacturing is a new technology for the industry. The machine has created an object for 3D layer by layer that makes a product with accurate dimensions and certain patterns, as the technology developed, the manufacturing industry began to develop products using additive material methods known as rapid prototyping or layer manufacturing, one of which was the use of 3D printer technology. This research was conducted on a 3D Printing FDM model Ender 3 Pro with dimensions 220 mm x 220 mm x 250 mm and using a nozzle with a 0,4 mm diameter. The material for this research is Nylon 6 with a diameter of 1,75 mm with variations in Layer Thickness (0,21 mm 0,24mm 0,27 mm), Infill Pattern (Rectilinear, Grid, Wiggle), Z-Orientation (0°,15°,30°) which will be determined in Ultimaker Cura 4.4.0 software and Taguchi Method in software minitab19.1. resulting in OA L9 with 3 times replication printed sample. The results obtained after testing the highest bending stress values are found in the 9th specimen which is 16,7 MPa average with 0,27 Layer Thickness, Wiggle Infill Pattern, and 15° Z-Orientation. While the lowest bending stress values are found in the 4th specimen which is 12,7 MPa average with 0,24mm Layer Thickness, Rectilinear Infill Pattern, and 15° Z-Orientation.